Fluorescent indicators for continuous and lineage‐specific reporting of cell‐cycle phases in human pluripotent stem cells. Issue 7 (22nd April 2020) - Chang, Yun; Hellwarth, Peter B.; Randolph, Lauren N.; Sun, Yufei; Xing, Yuxian; Zhu, Wuqiang; Lian, Xiaojun Lance; Bao, Xiaoping
Abstract: Proper cell‐cycle progression is essential for the self‐renewal and differentiation of human pluripotent stem cells (hPSCs). The fluorescent ubiquitination‐based cell‐cycle indicator (FUCCI) has allowed the dual‐color visualization of the G1 and S/G2 /M phases in various dynamic models, but its application in hPSCs is not widely reported. In addition, lineage‐specific FUCCI reporters have not yet been developed to analyze complex tissue‐specific cell‐cycle progression during hPSC differentiation. Desiring a robust tool for spatiotemporal reporting of cell‐cycle events in hPSCs, we employed the CRISPR/Cas9 genome editing tool and successfully knocked the FUCCI reporter into the AAVS1 safe harbor locus of hPSCs for stable and constitutive FUCCI expression, exhibiting reliable cell‐cycle‐dependent fluorescence in both hPSCs and their differentiated progeny. We also established a cardiac‐specific TNNT2‐FUCCI reporter for lineage‐specific cell‐cycle monitoring of cardiomyocyte differentiation from hPSCs. This powerful and modular FUCCI system should provide numerous opportunities for studying human cell‐cycle activity, and enable the identification and investigation of novel regulators for adult tissue regeneration. Abstract : A novel all‐in‐one, lineage‐specific fluorescent ubiquitination‐based cell cycle indicator (FUCCI) for continuous and lineage‐specific reporting of cell cycle phases is described in this study. Chang and coworkers have employed the CRISPR/Cas9 genome editing platform to establish stable human pluripotent stem cell (hPSC) FUCCI reporter lines, which can accurately track cell‐cycle patterns during mesoderm, endoderm, and ectoderm differentiation from hPSCs.